Rancang Bangun Prototype Sistem Kontrol Suhu dan Monitoring PH Air Pada Aquarium Benih Ikan Lele Dumbo Menggunakan Arduino UNO dan NodeMcu Berbasis IoT (Internet Of Things) - Hariyadi, Mohammad; Pramartaningthyas, Ellys Kumala; Ma'shumah, Siti; Salam, Mohammad Fikri Abdullah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2024)
Cultivation of Dumbo Catfish requires optimal water quality management to ensure healthy fry growth. Key parameters to monitor are water temperature and pH, as imbalances can negatively affect the health and growth of the fish. This study aims to design and develop a prototype water quality monitoring system based on the Internet of Things (IoT) using Arduino UNO and NodeMCU. In ideal cultivation conditions, the optimal water acidity (pH) ranges between 6–9, and the ideal water temperature is 26–30 °C. Using Arduino UNO and NodeMCU IoT technology, fish farmers can more easily control temperature and monitor water pH in the fry nursery aquariums. Arduino is the microcontroller, while the NodeMCU Wi-Fi module connects the microcontroller to the Blynk application as the user interface. Temperature regulation is achieved through water heaters and Peltier elements. Test results indicate that the system can maintain an average temperature of 26 °C and an average pH of 6, consistent with manual measurements using a water thermometer and litmus paper. The heating and cooling systems function optimally, with an average delay time of 13.5884298 milliseconds, significantly lower than the 150-millisecond threshold. Thus, the system operates effectively, facilitating fish farmers in real-time monitoring and controlling aquarium water quality.